BEHAVIORAL THERAPY TO REDUCE EMESIS IN PATIENT WITH PSYCHOGENIC VOMITING - Arif Rachman Hakim (Journal of Psychiatry Psychology and Behavioral Research, 2022)
Psychogenic vomiting or â€œfunctional vomitingâ€ is vomiting without any obvious organic pathology, resulting from psychological mechanisms. It is can occurs cause a result of an emotional disturbance or psychic disturbance without organic pathology. For the psychogenic vomiting treatment, there are previous treatment using pharmacotherapy, behavioral therapy, cognitive therapy, and supportive psychotherapy. Behavior therapy aim to changing the behavior in daily activities to reduce dysfunction and improve quality of life. Cognitive therapy aims to change psychological significance of peopleâ€™s beliefs about themselve, their personal world, and the future. Author used the literature review method by collecting several literatures that discuss about psychogenic vomiting, cognitive behavioral therapy, training behavioral therapy, and supportive therapy for psychogenic vomiting. The treatment should be directed to relieving intensity of vomiting episodes and improving the patientâ€™s health related to quality of life. The guideline of treatment of psychigenic vomiting remain unclear. Based on the literature, many various methods are used to treat psychogenic vomiting. Behavior therapy and cognitive therapy can be choosen to treat vomiting based on the underlying disease. All of the literature on psychogenic vomiting supports the use of a comprehensive, multi-disciplinary approach including pharmacological and psychotherapeutic treatment.Â Keywords: psychogenic vomiting, behavioral therapy, cognitive therapy.